Philosophical Approach to the Statutory Drafting - Škop, Martin (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
This article traces the relationship between the law-making process and narratives. Undoubtedly, how statutes are created is a constitutional question, yet the Constitution regulates only part of this process. Constitution or any statute does not regulate parts of the legislative process implemented by the government (mostly preliminary phases). However, they are important and influence the remaining parts of the law-making process. This government’s activity is the sphere of informal regulation hidden from the primary control of the public. This article explores the importance of the bureaucratic elements of the law-making process with emphasis on a narrative approach: narratives justify legislature. How can we overcome the two lines of narratives – one produced by global capital and the other represented by national experience?